Fatal work-related injuries in the Genoa district (North-Western Italy): Forensic analysis of the 10-year period between 2011 and 2020. (January 2022) - Errico, Stefano; Drommi, Martina; Calamano, Valentina; Barranco, Rosario; Molinari, Giulia; Ventura, Francesco
Abstract: According to the ILO (International Labor Organization), an occupational accident is that which occurs in the course of work and results in either a fatal or non-fatal injury. Occupational-related deaths are increasingly a concerning issue, also worldwide, with severe social repercussions: it is clear that when a person loses their life, it has a permanent impact on all their family, as well as incurring direct and indirect costs for employers, workers and the community at large. The aim of the present retrospective-observational study is to investigate, from an autoptic and forensic point of view, the characteristics of occupational-related deaths of victims received between the 10-year period of 2011–2020 by the Municipal Morgue of Genoa, which forms part of the Institute of Forensic and Legal Medicine, for the purpose of providing a Forensic and Coroner's overview of this important phenomenon. The study comprises of a list of 47 people who died as a result of an occupational injury: 46 males and 1 female. It was observed that workers in the construction and steel manufacturing industries were in the category most at risk of fatal accidents (40.5%). In 41 cases (87.2%), death was related to major mechanical trauma, from falling from a height (42.5%) objects falling directly onto the victim (38.3%) and lastly, from pedestrian road accidents (6.4%). Fatal head traumas with endocranial haemorrhage accounted for deaths in 23 of all the cases studied (63.4%). As shown in our study, death in the workplace is still today having to be considered as an important social issue and it is still necessary to improve the workers' knowledge of the related hazards and risks involved at work, together with preventative procedures. An in-depth analysis of such risks in the workplace, as well as the monitoring and training of workers is fundamental if we are to achieve an overall improvement in working conditions. Highlights: 47 people had died because of an occupational injury in Genoa from 2011 to 2020. The construction worker/metalworker was the most exposed to fatal accidents. In 41 cases (87.2%) the death is related to a major mechanical trauma. A fatal head trauma with endocranial haemorrhage occurred in 23 cases (63.4%). The toxicological screening resulted positive in only one case (alcohol) out of 47.